1D.02: COMPARATIVE EFFECT OF A RENIN INHIBITOR AND A THIAZIDE DIURETIC ON RENAL TISSUE OXYGENATION IN HYPERTENSIVE PATIENTS. (June 2015) - Vakilzadeh, N.; Muller, M.; Forni, V.; Milani, B.; Piskunowicz, M.; Zweiacker, C.; Vogt, B.; Pruijm, M.; Burnier, M.
Abstract : Objective: Renal tissue oxygenation may play an important role in the progression of renal diseases. Today, blockers of the renin-angiotensin system and diuretics are two major drug classes used to treat hypertension in patients with or without chronic kidney diseases. The purpose of the present study was to compare the direct renin inhibitor aliskiren to the diuretic hydrochlorothiazide (HCTZ) in their ability to modulate renal tissue oxygenation in hypertensive patients. Figure. No caption available. Design and method: Twenty four patients were enrolled in this randomized prospective study and 20 completed the protocol. Patients were randomly assigned to receive either aliskiren 150 titrated to 300 mg/d or HCTZ 12.5 mg titrated to 25 mg/d for 8 weeks. Renal oxygenation was measured by BOLD-MRI at weeks 0 and 8, 30 hours after the last dose. BOLD-MRI data were analyzed using the "onion peel" technique, a newly developed method which measures mean R2* levels in 12 computed layers of equal thickness in the kidney enabling to asses renal oxygenation according to the depth within the kidney, a higher R2* value corresponding to lower oxygenation. Results: Our results show that aliskiren tended to increase oxygenation in the outer (more cortical) layers and decreased oxygenation in the inner (more medullary) layers whereas HCTZ induced a significant overall decrease in renal tissue oxygenation (Figure 1). This latter finding may be due to the increased sodium reabsorption 30 h after the last dose of HCTZ (FELi: 21.2 ± 9% at W0 and 16.4 ± 6.0% at W8), p = 0.01). Patients responding to treatment by a fall in systolic blood pressure of >10 mmHg also increased renal tissue oxygenation when compared to non-responders. Conclusions: Taken together these results show that blockade of the renin-angiotensin system with aliskiren has a more favorable impact on renal tissue oxygenation in hypertensive patients than HCTZ. This finding may contribute to explain the renal protective effect of blockers of the renin-angiotensin system.